2017
DOI: 10.3389/fped.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Chest Compression Rate and Compression to Ventilation Ratio in Delivery Room Resuscitation: Evidence from Newborn Piglets and Neonatal Manikins

Abstract: Cardiopulmonary resuscitation (CPR) duration until return of spontaneous circulation (ROSC) influences survival and neurologic outcomes after delivery room (DR) CPR. High quality chest compressions (CC) improve cerebral and myocardial perfusion. Improved myocardial perfusion increases the likelihood of a faster ROSC. Thus, optimizing CC quality may improve outcomes both by preserving cerebral blood flow during CPR and by reducing the recovery time. CC quality is determined by rate, CC to ventilation (C:V) rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…American Heart Association recommends five components of high-quality pediatric cardiopulmonary resuscitation: ensuring CCs of adequate rate and depth, allowing full chest recoil between compressions, minimizing interruptions in CCs, and avoiding excessive ventilation [3,26]. The suboptimal quality of CCs with TFT was emphasized by several studies indicating that the only main advantage of TFT as compared with TTHT was optimal full chest relaxation [27].…”
Section: Discussionmentioning
confidence: 99%
“…American Heart Association recommends five components of high-quality pediatric cardiopulmonary resuscitation: ensuring CCs of adequate rate and depth, allowing full chest recoil between compressions, minimizing interruptions in CCs, and avoiding excessive ventilation [3,26]. The suboptimal quality of CCs with TFT was emphasized by several studies indicating that the only main advantage of TFT as compared with TTHT was optimal full chest relaxation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Along with high-quality CC, providing ventilation is important during neonatal CPR [19, 26]. Manikin studies reported higher ventilation rates during 3: 1 C:V compared to higher C:V ratios [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in numerous studies involving both children and adults, maintaining adequate CC frequency can be problematic because medical staff tend to perform CCs with too high a rate [18][19][20]. Moreover, the optimal frequency of CCs in both children and adults is not specified [21][22][23]. Li et al [24] showed that even though it was possible for neonatal staff to perform continuous CCs at rates of 90 and 120 × min -1 , a significant decay in CC pressure occurred after 96 s and 72 s, respectively.…”
Section: Discussionmentioning
confidence: 99%